2007
DOI: 10.1111/j.1439-0523.2007.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Drought effects on yield and its components in Indian mustard (Brassica juncea L.)

Abstract: Effects of drought on yield and yield components were investigated during the spring season 2000-2001 by growing 14 Indian mustard genotypes under irrigated and rain-fed conditions at Bharatpur and Jobner. A disease and pest management schedule was followed when required. The drought susceptibility index (DSI) for seed yield and component characteristics was calculated to characterize the relative tolerance of genotypes. Plant height, primary branches, secondary branches per plant, 1000-seed weight and seed yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 4 publications
3
26
1
Order By: Relevance
“…Because of they revealed minor yield reductions under drought condition. These results are in harmony with Chauhan et al (2007) and Kumar et al (2014). However, the development of different genotypes in relation to time of drought stress or shortage of adjustment with difficult conditions might due to the reason of variation in SSI.…”
Section: Mean Performance Of Genotypes Based On the Tolerance Indicessupporting
confidence: 91%
“…Because of they revealed minor yield reductions under drought condition. These results are in harmony with Chauhan et al (2007) and Kumar et al (2014). However, the development of different genotypes in relation to time of drought stress or shortage of adjustment with difficult conditions might due to the reason of variation in SSI.…”
Section: Mean Performance Of Genotypes Based On the Tolerance Indicessupporting
confidence: 91%
“…In addition to seed yield, drought stress also caused 20-40% reductions in SW, NPP, HFB and PH and <16% reductions in NPB, NSP and DM in the present study ( Table 2). Some of these results, however, conflict with a report in B. juncea, which found that SW was only marginally (5.3-6.0%) reduced under rain-fed conditions (Chauhan et al 2007). One explanation for the reduction in the values of agronomic characteristics for Brassica crops under rain-fed conditions is that the plants experienced decreased translocation of assimilates and growth substances, impairing nitrogen metabolism, inducing a loss of turgidity and, consequently, reducing sink size (Henry andMcDonald 1978, Kumawat et al 1997).…”
Section: Severe Natural Drought Revealed Drought-resistant Genotypescontrasting
confidence: 68%
“…The occurrence, duration and intensity of drought have profound impacts on rapeseed growth and production (Deepak and Wattal , Chauhan et al. ). Relative to non‐drought conditions, drought is associated with a significant loss of crop yield, shorter plant height, reduced oil content, fewer primary branches, lower 1000‐seed weight, fewer pods per plant and fewer seeds per pod but an increase in protein content (Maliwal et al.…”
mentioning
confidence: 99%
“…4 Location of associated markers for individual traits, identified by association mapping approach on the 18 chromosomes of B. juncea. Plheight plant height, secybranches number of secondary branches, rootdia root diameter A stress during any of these conditions tends to depress plant height and branch number and consequently the crop productivity due to a reduced number of pods/plant, premature flower fall and reduced seed number per pod (Chauhan et al 2007;Hosseini and Hassibi 2011). Studies have also shown that yield component compensation is an expected outcome of several inter-related traits sharing a common metabolic pool; nevertheless, there are reports of significant positive correlation between grain yield with secondary branches, plant height and seed size (Singh and Chowdhury 1983).…”
Section: Discussionmentioning
confidence: 98%